Elements to assess the quality of information of case reports in pregnancy pharmacovigilance data—a ConcePTION project - van Rijt-Weetink, Yrea R. J.; Chamani, Khoezik; Egberts, Antoine C. G.; van Hunsel, Florence P. A. M.; Lewis, David J.; Yates, Laura M.; Winterfeld, Ursula; van Puijenbroek, Eugène P. (Frontiers in Drug Safety and Regulation, 2023)
To assess the risk of exposure to a medicinal product during pregnancy in an individual case report, the necessary information should be present, complete and clearly described. Previously designed grading tools were not developed for pregnancy pharmacovigilance data. This study aims to identify the elements that are necessary to assess of the quality of information for risk assessment of medicinal products used during pregnancy. This is a first step in the development of a validated method to assess the clinical quality of case reports in pregnancy pharmacovigilance data. Potential information elements were determined by means of an expert focus group discussion and a survey based on its outcome. This provided an overview of possible information elements to be selected. For the final selection of the elements, a second survey and subsequent focus group discussion was used. Twenty-one information elements within seven categories were identified: information related to the association itself, the event, exposure to the medicinal product, maternal factors, pregnancy, labour, and the child. This study identified elements considered necessary in the assessment of quality of information of case reports in pregnancy pharmacovigilance data, via an extensive four-step process.